Attenuating susceptibility to ascites in cold‐stressed broiler chickens fed canola meal‐based diets by supplementing arginine or guanidinoacetic acid, either alone or in combination with phenylalanine - Negin Delfani; Mohsen Daneshyar; Parviz Farhoomand; Sina Payvastegan; Younes Ali Alijoo; Gholamreza Najafi (Veterinary Medicine and Science)
Abstract Objective The purpose of this study was to determine the effects of dietary supplementation of arginine (ARG) or guanidinoacetic acid (GAA), with or without phenylalanine (PHE), on the ascites susceptibility in the cold‐stressed broilers fed canola meal (CM)‐based diet. Method A total of 450 one‐day‐old male broiler chicks were randomly allocated to 30 floor pens with 6 replications for each of the 5 treatments. The dietary treatments were as follows: CM‐based diet (control), CM‐based diet + 2.57 g/kg ARG, CM‐based diet + 1.8 g/kg GAA, CM‐based diet + 2.57 g/kg ARG + 1.5 g/kg PHE and CM‐based diet + 1.8 g/kg GAA + 1.5 g/kg PHE. The groups experienced cold stress induction starting at 32°C on day one, with gradual reductions to 15°C on days 21. The temperature was then held at 15°C for the remainder of the experiment. Results The supplements ARG + PHE and GAA + PHE resulted in improved feed conversion ratios (FCR) when compared to the control group. In comparison with the control group, supplementation of ARG and ARG + PHE decreased the ascites mortality by increasing the plasma nitric oxide level (NO), blood O2 partial pressure, blood O2 saturation (SO2), and decreasing the blood CO2 partial pressure (PCO2) and right ventricle to total ventricle (RV:TV) ratio. Supplementation of GAA and GAA + PHE also declined ascites mortality by reducing blood PCO2 while increasing blood SO2 and plasma NO levels. Although plasma corticosterone level and RV:TV ratio were similar between the GAA and control groups, adding GAA + PHE significantly reduced both compared to the control group. Conclusion In summary, supplementing cold‐stressed broiler chicken diets with 2.57 g/kg ARG may alleviate hypertension. Additionally, 1.8 g/kg GAA proves to be an effective substitute for dietary ARG in low‐ARG diets, alleviating adverse effects from cold stress. Proper PHE formulation, at 1.5 g/kg in this study, is crucial when using ARG and GAA supplements.